The Blood Glucose Control And The Risk Of Diabetic Foot Ulcer In Type 2 Diabetes Mellitus - Eltrikanawati T. (Science Midwifery, 2022)
Uncontrolled diabetes mellitus can cause complications. One of the complications that is often encountered are diabetic foot ulcers. Diabetic foot ulcers are a common complication in people with Type 2 Diabetes Mellitus.The purpose of this study was to determine the relationship between blood glucose levels and the risk of diabetic ulcers in people with type 2 diabetes mellitus. Methods: This research is a type of analytical research used cross sectional design and Hypothesis test used Chi Square test. The results showed that from the results of the chi square statistical test, it was obtained that the value of = 0.000 (<0.05); OR= 4.2; 95%. The conclusion of the study showed that there was a significant relationship obtained from 52 people with type 2 diabetes mellitus, 17 respondents at risk of ulcers with uncontrolled blood glucose levels.The implication of this research is that it is hoped that health workers can schedule blood glucose level checks in type 2 Diabetes Mellitus patients and for Type 2 Diabetes Mellitus patients to be able to obediently control blood glucose levels to health services because regular blood glucose control can prevent complications of Type 2 Diabetes Mellitus, such as diabetic foot ulcers. Another very important factors about blood glucose control in people with diabetes mellitus for health workers is to pay more attention to adequate family support factor, psychological factor, social stigma factor, and cultural beliefs factor.